Internet connectivity disruption in Nicaragua (Nicaragua) - Voidly (2026)
CRITICAL severity disruption detected in Nicaragua. Confidence: 75%. Data sourced from IODA.
Network Disruption Incident ID: NI-2026-0014
Keywords: internet disruption; NI; disruption; critical